Investigation of the temperature distribution on the tool and workpiece during cryogenic machining of mg alloy by finite element analysis - Danish, M. (Asian Research Publishing Network, 2016)
Magnesium (Mg) alloys have always attracted researchers for being a light weight metal and now they have also found that it can also be used in the biomedical implants because of its compatibility with human body environment especially AZ31 Mg alloy. Machining of Mg alloy is a challenge itself because of its low melting point and ignition risks. Cryogenic machining can significantly reduce the temperature during machining. Which not only reduces the risk of ignition but also improved surface integrity of AZ31 Mg alloy. In this paper, a finite element analysis has been done to get the temperature distribution occur during the machining of Mg alloy. We have done the analysis in two different machining condition which were dry and cryogenic machining. The results have been validated from the experiments results and are found to be in good agreement. The temperature distribution at the tool surface and at the machined surface of the work piece were shown in the forms of coloured figures. Temperature distribution at the tool surface has been shown in the form of isothermal lines. In case of cryogenic machining, a notable decrease in the temperature was shown by the results. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.